Critical Synthesis Package: Self-Regulated Learning Perception Scale (SRLPS) - Tai Lockspeiser (Association of American Medical Colleges, 2013)
Abstract This Critical Synthesis Package contains: (1) a Critical Analysis of the psychometric properties and the application to health science education of the Self-Regulated Learning Perception Scale (SRLPS), and (2) a copy of the SRLPS instrument and the scoring instructions developed by Sevgi Turan, PhD. The SRLPS is a 41-item scale designed to measure medical students' self-regulated learning skills with a four factor structure consisting of: Motivation and Action to Learning, Planning and Goal Setting, Strategies for Learning and Assessment, and Lack of Self-Directedness. All 41 items are scored on a 5-point Likert scale from 1 (strongly disagree) to 5 (strongly agree). The total score ranges from 41 to 205. Higher scores on the scale indicate higher self-regulated learning skills. To date, there has been minimal validity evidence gathered to support the use of this scale, as only two studies with Turkish medical students have used it. This poses a particular challenge for use with English speaking students and supports the need for additional validity evidence using English speaking medical students from different countries. In addition, it would be helpful if the scale and dimensions were more directly connected with Zimmerman's model of self-regulated learning that suggests that there are three main sub-processes to learning: (1) forethought, (2) performance, and (3) self-reflection. Additional validity evidence for the relationship to other variables could be obtained by comparing scores on this scale with the Self-Directed Learning Readiness Scale, as that scale has been more widely studied in diverse populations of medical and nursing students, and assesses a similar construct.